Effects of EPSPS Copy Number Variation (CNV) and Glyphosate Application on the Aromatic and Branched Chain Amino Acid Synthesis Pathways in Amaranthus palmeri - Fernández-Escalada, Manuel; Zulet-González, Ainhoa; Gil-Monreal, Miriam; Zabalza, Ana; Ravet, Karl; Gaines, Todd; Royuela, Mercedes (Frontiers in Plant Science, 2017)
A key enzyme of the shikimate pathway, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS; EC 2.5.1.19), is the known target of the widely used herbicide glyphosate. Glyphosate resistance in Amaranthus palmeri, one of the most troublesome weeds in agriculture, has evolved through increased EPSPS gene copy number. The aim of this work was to study the pleiotropic effects of (i) EPSPS increased transcript abundance due to gene copy number variation (CNV) and of (ii) glyphosate application on the aromatic amino acid (AAA) and branched chain amino acid (BCAA) synthesis pathways. Hydroponically grown glyphosate sensitive (GS) and glyphosate resistant (GR) plants were treated with glyphosate three days after treatment. In absence of glyphosate treatment, high EPSPS gene copy number had only a subtle effect on transcriptional regulation of AAA and BCAA pathway genes. In contrast, glyphosate treatment provoked a general accumulation of the transcripts corresponding to genes of the AAA pathway leading to synthesis of chorismate in both GS and GR. After chorismate, anthranilate synthase transcript abundance was higher while chorismate mutase transcription showed a small decrease in GR and remained stable in GS, suggesting a regulatory branch point in the pathway that favors synthesis towards tryptophan over phenylalanine and tyrosine after glyphosate treatment. This was confirmed by studying enzyme activities in vitro and amino acid analysis. Importantly, this upregulation was glyphosate dose dependent and was observed similarly in both GS and GR populations. Glyphosate treatment also had a slight effect on the expression of BCAA genes but no general effect on the pathway could be observed. Taken together, our observations suggest that the high copy number variation of EPSPS in A. palmeri GR populations has no major pleiotropic effect on the expression of AAA biosynthetic genes, even in response to glyphosate treatment. This finding supports the idea that the fitness cost associated with EPSPS CNV in A. palmeri may be limited.